2008
DOI: 10.1038/sj.mp.4002146
|View full text |Cite
|
Sign up to set email alerts
|

A genome screen of 35 bipolar affective disorder pedigrees provides significant evidence for a susceptibility locus on chromosome 15q25-26

Abstract: Bipolar affective disorder is a heritable, relatively common, severe mood disorder with lifetime prevalence up to 4%. We report the results of a genome-wide linkage analysis conducted on a cohort of 35 Australian bipolar disorder families which identified evidence of significant linkage on chromosome 15q25-26 and suggestive evidence of linkage on chromosomes 4q, 6q and 13q. Subsequent fine-mapping of the chromosome 15q markers, using allele frequencies calculated from our cohort, gave significant results with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 54 publications
(53 reference statements)
0
21
0
Order By: Relevance
“…Canadian and Spanish data were kindly provided by Catherine Laprise (UQAC, Saguenay, Canada) and Manolis Kogevinas (CREAL, Barcelona, Spain). Genotyping of the samples Australia, Germany II, Germany III, and PGC-BD were described in previous studies 7,8,[42][43][44] . We aimed to genotype the patient and controls from the same population on the same chip type.…”
Section: Methodsmentioning
confidence: 99%
“…Canadian and Spanish data were kindly provided by Catherine Laprise (UQAC, Saguenay, Canada) and Manolis Kogevinas (CREAL, Barcelona, Spain). Genotyping of the samples Australia, Germany II, Germany III, and PGC-BD were described in previous studies 7,8,[42][43][44] . We aimed to genotype the patient and controls from the same population on the same chip type.…”
Section: Methodsmentioning
confidence: 99%
“…We and others have previously identified the 15q25–26 genomic region as harbouring a mental illness risk gene through linkage in family cohorts with bipolar spectrum disorder [16], bipolar disorder and schizophrenia [17], [18] or psychosis [19]. We subsequently found evidence of disease association with variants in ST8SIA2 in both bipolar disorder and schizophrenia [20].…”
Section: Introductionmentioning
confidence: 62%
“…Diagnosis was made by structured interview using the Diagnostic Interview for Genetic Studies (DIGS), using Research Diagnostic Criteria. To enrich for individuals who may have a genetic defect in ST8SIA2 , we selected one individual affected with bipolar disorder type 1 (BPI) or type 2 (BPII) (n = 39 and n = 3 respectively) from 42 families who showed evidence of linkage to chromosome 15q25–26 [16], and six additional unrelated BPI cases from our case-control cohort to ensure equivalent representation of major haplotypes to those observed in population samples [20]. A total of 45 BPI cases (94%) and three BPII cases (6%) formed the selected sample.…”
Section: Methodsmentioning
confidence: 99%
“…Continuing the theme of specific genes and their association with neural diseases, Professor Peter Schofield, Director of the Prince of Wales Medical Research Institute reported a significant link of chromosome locus 15q25-26 and susceptibility to bipolar disorder in 35 Australian multi-generational families [10]. He and his team have so far genotyped 376 single nucleotide polymorphisms at 15-kb resolution across the high-priority region and 20-kb resolution across the remaining 6.2-Mb interval in an Australian casecontrol cohort.…”
Section: Surprises From Particular Genes I N B R a I N D E V E L O P mentioning
confidence: 99%
“…He and his team have so far genotyped 376 single nucleotide polymorphisms at 15-kb resolution across the high-priority region and 20-kb resolution across the remaining 6.2-Mb interval in an Australian casecontrol cohort. The gene ST8SIA2, previously associated with schizophrenia in Japanese and Chinese patients, was identified as a putative bipolar susceptibility gene within the 15q25-26 linkage region [10].…”
Section: Surprises From Particular Genes I N B R a I N D E V E L O P mentioning
confidence: 99%